Integrated Framework for Decentralized Renewable Energy and Wastewater Treatment Plant Coupling to Achieve Sustainable Circular Nexus in Urban Communities - Beny Riswanto; Rahmadi Agus; Sofiansyah Fadli (Green Engineering: International Journal of Engineering and Applied Science, 2024)
Urban sustainability presents considerable challenges, especially in the management of energy and wastewater treatment systems. Rapid urbanization intensifies the demand for water and energy, leading to increased pressure on existing infrastructure and resources. Wastewater management is essential for urban water sustainability, as untreated wastewater poses significant environmental and health risks. Moreover, wastewater treatment processes are energy-intensive, complicating the balance between environmental goals and energy consumption. To address these challenges, integrating decentralized renewable energy systems, such as solar, biogas, and wind, with wastewater treatment plants (WWTPs) offers a promising solution. This integration can reduce reliance on centralized power grids, enhance energy self-sufficiency, and promote sustainability. The application of Circular Economy principles, which emphasize resource recovery and system decentralization, is key to this integration. However, technological, economic, and regulatory barriers exist, limiting widespread adoption. This study explores the feasibility of coupling renewable energy with WWTPs, focusing on energy flow simulations, environmental impacts, and economic evaluations. The results indicate that integrating renewable energy can significantly reduce greenhouse gas emissions, lower operational costs, and improve the resilience of urban water systems, making it a viable option for sustainable urban development.